Integralisasi Agama dan Sains di Lembaga Pendidikan Islam - Ali Muhdi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: The problem of separation or dichotomy between religious knowledge and scientific knowledge held by general educational institutions and religious educational institutions cause us trapped in crisis. As a result, the orientation of Islamic education is ambivalent. The mu’amalah or ibadah in extensive meaning which covers various scientific disciplines and expertise in considered as non Islamic studies territory, but as the territory of secularistic educational system. Keywords: Integration, Islamic Educaion, Progressive.